Endowing BIM Model with Mechanical Properties -- Finite Element Simulation Analysis of Long-Span Corrugated Steel Web Continuous Beam Bridge. Issue 1 (1st February 2022) - Zhang, X Y; Qu, Q L; Liang, D; Liu, T C
Abstract: Taking the main bridge of Zhaojun Yellow River Super Large Bridge as the engineering background, this paper explores the application of BIM technology in the finite element simulation analysis of long-span corrugated steel web continuous beam bridge, and proposes to establish the model of corrugated steel web continuous beam bridge by using the parametric modeling method of Revit software, Dynamo visual programming software is used to extract the geometric parameter information of BIM model, and the method of data conversion between BIM model and finite element model is realized through Python language programming, so as to endow BIM model with mechanical properties, avoid repeated modeling, and improve modeling efficiency and accuracy. The finite element simulation of the converted model in Midas/Civil provides and support for bridge construction monitoring, and provides new ideas for the application of BIM technology and structural calculation in similar projects.